The genetic basis for elite running performance - Tucker, R.; Santos-Concejero, J.; Collins, M. (British Journal of Sports Medicine, 2013)
The dominance of East African distance runners and sprinters of West African origin invites discussion around the contribution of genetic and lifestyle factors to performance. In this review, we focus on the genetic basis for performance. Previous research associating candidate genes such as ACE and ACTN3 to endurance and sprint performance in Caucasian populations has not been replicated in African populations. This may be influenced by numerous factors, including small sample sizes, comparisons across different ethnic populations and problems identifying appropriate control groups. Conceptually, these failures reveal the complex polygenic nature of physiology and performance, and the erroneous application of a candidate gene approach to more genetically diverse African populations. We argue that research has in fact established a role for genes in performance, and that the frequency, rather than the prevalence, of favourable genetic variants within certain populations may account for the performance dominance in these populations.